LncRNA SNHG1 Promotes the Progression of Pancreatic Cancer by Regulating FGFR1 Expression via Competitively Binding to miR-497 - Chen, Shihong; Guo, Wenyi; Meng, Mingyang; Wu, Dong; Zhou, Tao; Wang, Lei; Xu, Jianwei (Frontiers in Oncology, 2022)
Background: Long noncoding RNA small nucleolar RNA host gene 1 (SNHG1) is dysregulated in a variety of tumors. However, little is known of its role in pancreatic cancer (PC). Methods: The role of SNHG1 on PC cell proliferation, migration, invasion, apoptosis, and the epithelial-mesenchymal transition (EMT) were assessed in vitro using MTT, EDU, wound healing, and Transwell assays, as well as flow cytometry and western blotting. Luciferase reporter assay, western blotting, and qRT-PCR were used to examine SNHG1 regulation. Tumor growth in mice was also investigated. Results: Downregulation of SNHG1 blocked cell proliferation, migration and invasion, and induced apoptosis in vitro, while also inhibiting the EMT, shown by changes in the biomarkers E-cadherin, N-cadherin, and Vimentin. The opposite results were observed on upregulation of SNHG1. In vivo experiments showed that downregulation of SNHG1 inhibited tumor development in nude mice. Furthermore, experiments investigating the regulatory mechanism of SNHG1 indicated that SNHG1 acted as a competitive endogenous RNA, positively regulating the expression of fibroblast growth factor receptor 1 (FGFR1) through sponging miR-497. Rescue experiments demonstrated that the effects of SNHG1 downregulation on PC cells were attenuated when simultaneously inhibiting the levels of miR-497. Conclusions: SNHG1 upregulates FGFR1 expression by sponging miR-497, which promotes the progression of PC. SNHG1 may thus be a novel target for treating PC.